(untitled) (Global Journal of Science Frontier Research, 2015)
A decade ago in August 2005 Hurricane Katrina devastated north-central Gulf of Mexico and southeastern Louisiana and Mississippi Gulf Coast. Although nearly all anemometers in the affected areas were destroyed by Katrina, few wind and wave measurement stations did survive the storm and provide some data to advance our understanding of the physics of air-sealand interaction. Analyses of these measurements indicate that : 1. On the basis of upper-air measurements made at Key West, FL, and Slidell, LA, the power-law wind profile is verified in the atmospheric surface boundary layer (up to 300m) where the friction dominants; 2. The cyclostrophic equation, which is the balance between centrifugal force and pressure gradient force, is validated so that the wind speed at 10m over the water, U10 = 6.3(1013 -Pmin) ^ (1/2), where Pmin is the minimum sea-level pressure; 3.The significant wave height (Hs) and its dominant wave period (Tp) can be normalized by using U*, which is the friction velocity (= (τ/ρ) ^ (1/2), where τ is the wind stress and ρ is the air density).